Knowledge and behaviour towards second hand smoke exposure among high school teachers in Davanagere city: a cross sectional survey - Yavagal, Puja C.; Susheelamma, Mahalaxmi H.; Shivashankar, Sumukh; Nagabhushanaiah, Vinitha D.; Pawaskar, Sonia R.; Maruthi, Sushma G. (International Journal Of Community Medicine And Public Health, 2022)
Background: School teachers may influence the avoidance of smoking and second-hand smoke (SHS) exposure behaviour in their students. Objective was to assess the knowledge and behaviour of high school teachers towards SHS in Davanagere city. Methods: A cross sectional questionnaire survey was conducted in the school setting involving a stratified random sample of 160 high school teachers in Davanagere city. A pre validated 18 item questionnaire was used to collect data with responses on 5-point Likert scale. The questionnaire was tested for face validity, language validity and content validity (content validity index score for relevance clarity, simplicity and ambiguity was 0.87, 0.84, 0.92, and 0.94, respectively). The significant level was fixed at p<0.05. Descriptive data was expressed in frequencies. Statistical analysis was done using Student’s unpaired ‘t’ test, one-way analysis of variance (ANOVA) and Pearson’s/Spearman’s correlation tests. Results: The mean age of teachers was 37.59±9.56 years with average teaching experience of 10.72±8.02 years. The mean knowledge and behaviour scores of participants were 29.65±4.94 and 31.56±4.28 respectively which reflected good knowledge and behaviour towards SHS. Knowledge and behaviour scores of participants were significantly (p<0.05) correlated with age (r=-0.19, -0.26), sex (r=0.21, 0.27) and teaching experience (r=-0.17, -0.23). Knowledge scores were positively correlated with behaviour scores (r=0.52, p=0.00). Conclusions: High school teachers in Davanagere city had good knowledge about and behaviour towards SHS.